Application of rice husk biochar as soil amendment for improvement of rice yield, nutrient uptake, soil properties and fertilizer nitrogen recovery - Sang, Deniel (2017)
The excessive rice husk produced after each rice (Oryza sativa) harvesting period poses a severe threat to environmental and human health. In Malaysia, about 408, 000 Mg per annum of rice husks produced and only a small percent of rice husks is used as a source of heat energy for drying process and produced a by-product known as rice husk char (RHB). Although few studies have validated benefits of RHB application, no study regarding the RHB application effects on rice yield parameter, soil properties and fertilizer nitrogen recovery have been done in Malaysia. Thus, a field experiment was conducted in Barat Laut Selangor (BLS) at Sungai Burong, Tanjong Karang, Selangor to determine the effects of RHB on rice yield parameters and soil properties for two crop cycles. Four rates of RHB treatment 0, 5, 10 and 20 Mg ha-1 was laid out in RCBD with 4 replications. Soil is classified as Sulfic Endoaquepts (Sabrang series) with organic matter content of 17%. Results indicate that biochar significantly improved the soil chemical properties in general, particularly total C after second crop cycle compared to the control (without RHB). Also, N, P and K uptake was significantly (P≤0.05) improved under RHB treatment in both crop cycles. More importantly, rice grain yield also significantly (P≤0.05) increased with RHB application compared to control, with an increment of 44% in the first cycle and 45% in the second cycle. Biochar application significantly (P≤0.05) enhanced percent productive tiller, panicle length and weight per panicle in both crop cycles. A pot study was also carried out at Field 10, UPM, Serdang to investigate the effectiveness of RHB on urea nitrogen recovery under controlled condition. Results of this experiment show that RHB application although significantly (P<0.05) improved soil properties, shoot and root dry matter weight and nutrient uptake 75 days after application. Application of urea-N recovery in shoot was not significantly higher than control with ranged of 40.97 to 41.64% of applied N.